Redefining the polypill: pros and cons in cardiovascular precision medicine - Birla, Siddharth; Angural, Arshia; Madathumchalil, Arya; Shende, Ritika V.; Shastry, Sharvani V.; Mahadevappa, Manjappa; Shambhu, Sunil Kumar; Vishwanath, Prashant; Prashant, Akila (Frontiers in Pharmacology, 2023)
Polypill is a multi-drug formulation in a single pill intended to simplify the drug regimen and reduce medication-induced adverse effects. The most common multidrug combinations in a polypill are used to treat cardiovascular diseases and are targeted against key modifiable risk factors such as hypertension and hyperlipidemia. These contain blood-pressure lowering agents, statins, and anti-platelet agents usually in a fixed dose. Polypills can be an affordable therapeutic intervention for treating high-risk patients, as these are proven to increase patients' adherence to medication and improve clinical outcomes. Over the previous years, randomized clinical trials of several polypills have yielded contradictory findings, raising skepticism regarding their widespread use in primary disease prevention. Here, we have reviewed the concept of polypills, the evidence-based strengths, the limitations of this polypharmacy intervention strategy, and discussed future directions for their use in the primary and secondary preventive management of cardiovascular diseases and associated risk factors.